Infrasound - the cause of strong Polar Mesosphere Winter Echoes? - S. Kirkwood; P. Chilson; E. Belova; P. Dalin; I. Häggström; M. Rietveld; W. Singer (Annales Geophysicae, 2006)
The ESRAD 52-MHz and the EISCAT 224-MHz radars in northern Scandinavia observed thin layers of strongly enhanced radar echoes from the mesosphere (Polar Mesosphere Winter Echoes - PMWE) during a solar proton event in November2004. Using the interferometric capabilities of ESRAD it was found that the scatterers responsible for PMWE show very high horizontal travel speeds, up to 500 ms -1 or more, and high aspect sensitivity, with echo arrival angles spread over as little as 0.3°. ESRAD also detected, on some occasions, discrete scattering regions moving across the field of view with periodicities of a few seconds. The very narrow, vertically directed beam of the more powerful EISCAT radar allowed measurements of the spectral widths of the radar echoes both inside the PMWE and from the background plasma above and below the PMWE. Spectral widths inside the PMWE were found to be indistinguishable from those from the background plasma. We propose that scatter from highly-damped ion-acoustic waves generated by partial reflection of infrasonic waves provides a reasonable explanation of the characteristics of the very strong PMWE reported here.